Report of a real-time pcr assay for paenibacillus larvae dna detection from spores of scale samples - Quintana, S. (2017)
The Gram-positive bacterium Paenibacillus larvae is one of the major pathogens of Apis mellifera, causing the disease knownas American foulbrood. Identification of P. larvae by microbiological methods can be difficult and time consuming. We reporta real-time PCR assay that could be successfully used for rapid and specific detection of P. larvae DNA in bacterial pure culturesand directly from scale samples.